The Important Role Of Islamic Boarding Schools in Forming Islamic Leadership - Yuyun Bahtiar; Mohammad Nuril Anwar; Iin Baroroh Ma'Arif; Luluk Choirun Nisak Nur; Ulfa Wulan Agustina (SCHOOLAR: Social and Literature Study in Education, 2025)
Islamic Boarding Schools have an important role in the formation of Islamic leadership and in producing graduate students as faithful people, pious, have noble morals, and follow the teachings of the Prophet Muhammad SAW. Especially able to emulate and apply the leadership of the Prophet SAW which prioritizes leadership theory based on the values ​​of Shiddiq, Tabligh, Amanah, and Fathanah. This study aims to find out the learning strategies applied at the Kalaga Al-Kamal Islamic Boarding School Denanyar Jombang, the important role of boarding schools in forming students in Islamic leadership so that they can lead, direct, train, organize well to achieve the planned goals based on the values ​​of the Al-Quran and Sunnah, and analyze the factors, namely supporting and inhibiting factors that influence effective leadership at the Kalaga Al-Kamal Islamic Boarding School Denanyar Jombang. Data collection was carried out through observation, interviews, and documentation. The types and methods used are qualitative methods using data collection interviews, observations, and documentation. The results of this study indicated that the leadership of the Kalaga Al-Kamal Islamic Boarding School Denanyar Jombang and teachers in guiding and providing knowledge were very important for students on how to become competent, responsible, forward-looking students, inspire many people, always were trustworthy, honest, and humble.